S737F is a new CFTR mutation typical of patients originally from the Tuscany region in Italy - Vito Terlizzi; Antonella Miriam Di Lullo; Marika Comegna; Claudia Centrone; Elisabetta Pelo; Giuseppe Castaldo; Valeria Raia; Cesare Braggion (BMC, 2018)
Abstract Background An increasing number of patients have been described as having a number of Cystic Fibrosis Transmembrane conductance Regulator (CFTR) variants for which it lacks a clear genotype-phenotype correlation. We assesses the clinical features of patients bearing the S737F (p.Ser737Phe) CFTR missense variant and evaluated the residual function of CFTR protein on nasal epithelial cells (NEC). Methods A retrospective database was performed from individuals homozygous or compound heterozygous for the S737F variant followed in the Cystic Fibrosis (CF) Centre of Florence. We performed a nasal brushing in cooperating patients and compared the results with those of patients followed in the pediatric CF Centre of Naples. Results 9/295 (3%) subjects carrying at least S737F CFTR variant on one allele were identified. Patients were diagnosed in 7/9 cases by newborn screening and in two cases for dehydration with hypochloremic metabolic alkalosis; at diagnosis sweat chloride levels (SCL) were in the pathological range in only one case. After a mean follow up of 8,6 years (range 0,5-15,8), SCL were in the pathological range in 8/9 cases (mean age at CF diagnosis: 1,5 years), all patients were pancreatic sufficiency and respiratory function was normal. The gating activity on NEC was 15.6% and 12.7% in two patients compound heterozygous for W1282X and DelE22_24, while it was ranged between 6,2% and 9,8% in CF patients. Conclusions S737F is a CFTR mutation associated to hypochloremic alkalosis in childhood, mild CF phenotype in teenage years and a residual function of CFTR protein.